Be glad your nose is on your face and other poems : some of the best of Jack Prelutsky - Prelutsky, Jack; Dorman, Brandon (New York : Greenwillow Books, 2008)
Selection of poems by Jack Prelutsky, America's first Children's Poet Laureate.
Collects more than 100 of the popular author's poems, spanning his forty-five year career as a master funny-bone tickler and the bard of choice for elementary school children everywhere! Features a CD with classic performances by the poet himself.
CD: The egg (1:27) -- We're four ferocious tigers (1:15) -- It's hard to be an elephant (3:08) -- Chitterchat (3:18) -- My mouse is out (2:23) -- The frogs wore red suspenders (1:38) -- I saw a brontosaurus (3:06) -- Ballad of the boneless chicken (2:39) -- The detested radishark (1:41) -- The solitary spatuloon (1:45) -- My mother made a meatloaf (3:24) -- Worm puree (4:39) -- Song of the lizard lovers (2:14) -- Eyeballs for sale! (1:51) -- A pizza the size of the sun (2:36) -- Rat for lunch! (2:30) -- Percy's perfect pies (2:28) -- Song of the gloopy gloppers (2:09) -- Happy birthday, dear dragon (3:15) -- Once they all believed in dragons (2:55) -- We're seven grubby goblins (2:13) -- We're fearless flying hot dogs (3:16) -- I sailed on half a ship (1:50) -- Overheard at the zoo (0:48) -- Cecil Jessel (0:30) -- If (3:27) -- Be glad your nose is on your face (1:12) -- They never send Sam to the store anymore (2:30) -- I wash my shadow weekly (0:47) -- I wished into a wishing well (1:21)
Includes activities and indexes.
Keywords: Children's poetry, American; Poetry, American